Perencanaan Strategi Sistem Informasi untuk Peningkatan Layanan Administrasi Berbasis Ward and Peppard dan AHP - Intan Sari Gusti; Alva Hendi Muhammad; Dony Ariyus (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2026)
This study aims to formulate an information systems strategy to optimize an administrative service owned by LPK Techno Flash. The main problems that can be identified include minimal administrative operational efficiency due to unnecessary repetition in processes and data, minimal integration between systems, which results in service delays and decreased user satisfaction. This study utilizes a combined approach between the Ward & Peppard framework for gap analysis and strategy formulation, and the Analytic Hierarchy Process (AHP) method to determine strategy priorities. The Ward & Peppard analysis includes an evaluation of the internal and external environment, analysis of application documentation, and identification of business and information system strategy needs. The results of this study provide structured information system strategic recommendations, including information management strategies, application strategies, and technology strategies. The strategic priorities obtained from AHP will serve as the basis for LPK Techno Flash in planning and implementing integrated information system solutions, increasing effectiveness, and supporting improvements in overall service quality and user satisfaction.